Effect of Public Broadcast on Public Knowledge of Preconception Folic Acid Towards Birth Defect Prevention in Malaysia - Tan Beng Geok; Soon Lean Keng; Nor Azwany Yaacob; Hans Van Rosternberghe (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Health promotion is essential for influencing behaviour change to prevent birth defects and achieve the Sustainable Development Goal of reducing neonatal and under-five mortality by 2030. Public broadcasting has the potential to deliver health messages widely, particularly in underserved communities, but evidence from interrupted time series (ITS) studies remains limited. This study aims to evaluate the impact of public broadcast interventions on knowledge of preconception folic acid intake for birth defect prevention in Malaysian using an interrupted time series (ITS) design. This study used an ITS design. Data were collected fortnightly at six time points over 12 weeks from 2,832 adults aged 18–64 years, recruited via convenience sampling. Participants were equally divided between an intervention group in Kelantan (n = 1,416), where targeted radio and television messages were broadcast, and a control group in Terengganu (n = 1,416), which received no intervention. Knowledge was measured using a standardised questionnaire. Segmented regression analysis showed a descriptive increase in mean knowledge scores post-intervention in the intervention group. However, no statistically significant changes were observed in trend (slope change = 0.0006) or level (intercept change (<–0.01) between pre- and post-intervention phases. While statistical significance was not achieved, the findings indicate that public broadcasting is a promising medium for large-scale health promotion, capable of reaching broad audiences and addressing knowledge gaps. These results provide baseline evidence for designing future national-level broadcast interventions, which may require longer exposure periods or intensified messaging to achieve significant and sustained improvements in public health knowledge.